2019
DOI: 10.32737/0005-2531-2019-4-27-31
|View full text |Cite
|
Sign up to set email alerts
|

Co(II), Ni(II), Cu(II) COMPLEXES WITH 1-NICOTINOIL-2-(2-HYDROXYBENZYL) HYDRAZINE

Abstract: By reduction of 1-nicotinoyl-(2-salicylidene)hydrazone with use NaBH 4 1-nicotinoyl-2-(2-hydroxybenzyl)hydrazine was obtained. Co(II), Ni(II), Cu(II) complexes with these ligands were synthesized and their structure was studied. It was shown that first ligand behaves as a dianionic tridentate, while second is monoanionic tridentate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Previously, we have found that metal complexes of hydrazones of salicylic acid derivatives have signi cant inhibitory and urease activity [19]. At the same time, succinic and nicotinic acid hydrazones and their complexes have high bactericidal and fungicidal activity [20,21].…”
Section: Introductionmentioning
confidence: 98%
“…Previously, we have found that metal complexes of hydrazones of salicylic acid derivatives have signi cant inhibitory and urease activity [19]. At the same time, succinic and nicotinic acid hydrazones and their complexes have high bactericidal and fungicidal activity [20,21].…”
Section: Introductionmentioning
confidence: 98%
“…[14,15]. Previously, we found that metal complexes of hydrazones of salicylic acid derivatives have significant inhibitory and urease activity [16], succinic and nicotinic acid hydrazones and their complexes have high bactericidal and fungicidal activity [17,18].…”
mentioning
confidence: 99%